THE PHOTOELASTICITY OF RHOMBIC SYNGONY CRYSTALS - Vasyl Stadnyk; I. Matviishyn; N. Ftomyn; V. Vyshnevskyi; V. Baliga; O. Shtuka (Електроніка та інформаційні технології, 2024)
The Rb2SO4 crystals were synthesized by slow evaporation of room-temperature aqueous solution of pure rubidium sulfate salts that had been recrystallized many times. The solution temperature was 310 K, controlled by a thermostat with an accuracy of 0.5 K.